Boemerang swingt de wereld over : een aktiviteitenaanbod vor jong Nederland junioren (10-13 jaar) - Mommers, Irma; van Zundert, Alex; Vestjens, Hans ([S.l]: Novib; JN, 1993)
"Irma Mommers; Alex van Zundert; Hans Vestjens... et al."